Renal BOLD-MRI does not reflect renal function in chronic kidney disease - Michaely, Henrik J. M.; Metzger, Linda Madeleine; Haneder, Stefan; Hansmann, Jan; Schönberg, Stefan; Attenberger, Ulrike (Kidney international, 2012)
Renal blood oxygen level-dependent magnetic resonance imaging (BOLD-MRI) is a noninvasive fast technique to characterize renal function. Here we evaluated the impact of renal function on the relaxation rate (R2*) in the cortex and medulla to provide baseline data for further use of renal BOLD-MRI. This parameter was evaluated in 400 patients scheduled for abdominal imaging who underwent transversal blood oxygen level-dependent measurements with a multi-echo gradient-echo sequence with 12 echo times. The loss of phase coherence (T2*) maps were generated in which kidney regions of interest were selected to differentiate the medulla and cortex, and R2* was equated to 1/T2*. Individual R2* values were, in turn, correlated to the eGFR (MDRD formula of 280 patients with available serum creatinine measurements), age, and gender each for 1.5 and 3.0T field-strength scans of 342 patients. At both the field strengths, no significant differences in R2* of the cortex and medulla were found between patient gender, age, eGFR, or between different stages of chronic kidney disease determined using the KDOQI system. Thus, BOLD-MRI of a non-specific patient population failed to discriminate between the patients with various stages of chronic kidney disease.